Association between tobacco smoking and prognosis of occupational hand eczema: a prospective cohort study. (1st November 2014) - Brans, R.; Skudlik, C.; Weisshaar, E.; Gediga, K.; Scheidt, R.; Wulfhorst, B.; Elsner, P.; Schönfeld, M.; John, S.M.; Diepgen, T.L.
Summary: Background: Hand eczema (HE) is a common occupational skin disease. Tobacco smoking is known to be associated with adverse cutaneous effects. However, its influence on the prognosis of occupational HE has not yet been studied. Objectives: To evaluate relations between smoking status, severity and prognosis of occupational HE in patients taking part in an interdisciplinary tertiary individual prevention programme (TIP). Methods: In a prospective, multicentre, cohort study 1608 patients with occupational HE taking part in a TIP were recruited and followed up for 3 years. The clinical and self‐reported outcome data of smokers and nonsmokers were compared. Results: Nonsmokers and smokers were equally distributed. During the TIP, the average self‐reported daily cigarette consumption and the severity of HE decreased significantly ( P < 0·01). However, at all time points HE was significantly more severe in smokers than in nonsmokers. This association was not dependent on the self‐reported number of cigarettes smoked daily. Smokers had significantly more days of absence from work due to occupational HE than nonsmokers in the year before the TIP ( P < 0·01) and in the following year ( P = 0·02). After the TIP, smokers reported significantly more often that they had to give up their occupation ( P = 0·02) than nonsmokers. Conclusions: The severity of occupational HE is increased in smokers. Tobacco smoking is associated with a higher number of days of absence from work and with not staying in the workforce owing to occupational HE. Thus, smoking confers a worse prognosis and interferes with the outcome of prevention programmes.